An M2M cognitive MAC protocol for overlaid OFDMA environments. Issue 3 (19th June 2015) - Tarchi, Daniele; Fantacci, Romano; Marabissi, Dania
Abstract: Machine to machine (M2M) communications have gained in the last years an increasing interest due to ever growing number of machine‐type devices that are used in different application fields by allowing low cost and efficient communications among devices mainly in an autonomous manner. Even if M2M protocols need of dedicated resources, a new paradigm called cognitive M2M (CM2M) has been recently introduced in order to exploit cognitive/opportunistic radio communications. The aim of this paper is to outline a CM2M mechanism, where the primary network is based on the orthogonal frequency division multiple access technique, while the M2M communication‐based secondary network uses a novel medium access control technique, named data aided cognitive technique (DACT). The performance of the proposed DACT protocol is derived by means of suitable analytical methods under different operational conditions. Analytical predictions are also validated by comparisons with numerical results obtained through computer simulations, in order to show the effectiveness of the proposed solution in terms of throughput, delay, resource wastage and CM2M devices queue length; to this aim, the proposed DACT protocol has been implemented with different alternatives. Among them, an adaptive approach allows to optimise the system performance by increasing the overall throughput while keeping under control the system delay and the resource wastage. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Machine to machine (M2M) communications have gained in the last years an increasing interest due to ever growing number of machine‐type devices. Even if M2M protocols need of dedicated resources, a new paradigm called cognitive M2M has been recently introduced in order to exploit cognitive/opportunistic radio communications. We propose here a cognitive M2M mechanism, where the primary network is based on the orthogonal frequency division multiple access technique, while the M2M communication‐based secondary network uses a novel medium access control technique, named data‐aided cognitive technique.